4-[(1,5-Dibenzyl-2,4-dioxo-2,3,4,5-tetrahydro-1H-1,5-benzodiazepin-3-y l)methyl]-1-n-octyl-1H-1,2,3-triazole - Jabli, H.; Chahdi, F.O.; Saffon, N.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The reaction of 1,5-dibenzyl-3-propargyl-1,5-benzodiazepine-2,4- dione with 1-azido-n-octane in the presence of catalysts leads to the formation of the title compound, C(34)H(39)N(5)O(2), which features a phenylene ring fused with a seven-membered diazepinyl ring. The latter ring adopts a boat conformation with the octyltriazolylmethyl-bearing C atom as the prow and the fused-ring C atoms as the stern. The octyltriazolylmethyl substituent occupies an axial position.